ALIH KODE DAN CAMPUR KODE DALAM DRAMA CHEONGDAMDONG ALICE : KAJIAN SOSIOLINGUISTIK - , RONA MENTARI SAIDI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Code-mixing and code-switching are chosen to be the formal object of this research because a code-mixing and code-switching study on Korean drama in Gadjah Mada University study has never been done before. Data analysis is done by descriptive method. Cheongdam-dong Alice is suitable for the research since its rich with code-mixing and code-switchingâs usage such as English, Indian, Japan, and France. This research aims to (1) specify code-mixing and codeswitchingâs nature on all ten episodes of Cheongdam-dong Alice drama, (2) identify the kind of code-mixing and code-switching on Cheongdam-dong Alice drama, and (3) analyze the factors that caused code-mixing and code-switchingâs usage in Cheongdam-dongâs Alice drama which being carried by the characters on first episode to tenth episode. The nature of code-mixing in the object material is both temporary and permanent, meanwhile the nature of code-switching is temporary as found out on the research. The kind of code-mixing and codeswitching on Cheongdam-dong Alice drama is external. There are 4 (four) factors that caused code-switching, such as the speaker, the hearer, the shift from formal to informal viceversa, and topic change. Whereas there is 5(five) causes that is being found, for instance (1) low frequency or word , (2) pernicious homonymy, (3) need for synonym, (4) the development or introduction with new culture, and (5) social value.